MEMS Sensors Design and Application - Yellampalli, Siva (IntechOpen, 2018)
MEMS by becoming a part of various applications ranging from smartphones to automobiles has become an integral part of our everyday life. MEMS is building synergy between previously unrelated fields such as biology, microelectronics and communications, to improve the quality of human life. The sensors in MEMS gather information from the surrounding, which is then processed by the electronics for decision-making to control the environment. MEMS offers opportunities to miniaturize devices, integrate them with electronics and realize cost savings through batch fabrication. MEMS technology has enhanced many important applications in domains such as consumer electronics, biotechnology and communication and it holds great promise for continued contributions in the future. This book focuses on understanding the design, development and various applications of MEMS sensors.